Design Considerations of Online Infertility Prevention Training (OIPT): Development and Evaluation - Bahar Baran; Sirin Nur Yaci; Murat Ocal; Digdem Muge Siyez (Journal of Education in Science, Environment and Health)
Health-related internet sources should contain accurate, reliable and updated information, and their usability should be high to enable people to navigate successfully. This study aimed to develop interactive Online Infertility Prevention Training (OIPT) and to reveal design principles by evaluating the online training. The development, design, and redesign processes of this study included four iterations: 1) needs analysis, 2) implementation as a usability test, 3) implementation with the target group in a class, and 4) comparison of iteration II and III, and decision; and two outputs. The research process included the participation of the target audience in the design process and there were continuous corrections to the design. In the study, a design-based research approach was used. In the qualitative dimension, the data was collected with “User Information Form”, “System Usability Observation Form”, and the system usability interview form, and task cards. In the quantitative dimension, Infertility Knowledge Test, System Usability Scale, and also database records were used. The data obtained from tools were analyzed descriptively and predictively. As a result, this research claimed that design, development, and evaluation belong to health-related sources on the Internet should include field design principles and techniques and specific methods, although designers use prevalent techniques. The results indicated that gender’s effect on media and material design, the importance of the use of expert authority in the presentation of content knowledge that system usability significantly increased from iteration two to three. Therefore, gender differences in media and material preferences except for content knowledge and also expert views may be considered in the design of health-related online training. In addition, while teaching concrete parts of the human body, interactive animations and visuals may be useful to motivate and increase engagement students to use the content again and again. Furthermore, the results of this study show that feedback design is crucial in the navigation of online learning environments. Overall, this study strengthens the idea that while designing online education environments, it is important to determine users’ needs and expectations at first, afterwards conducting usability tests to specify the design challenges.